Policy towards Commodity Shocks in Developing Countries - Gunning, Jan (IMF Working Papers; Working Paper ;, 1996)
On the basis of a comparative study of 23 episodes involving commodity price shocks we find that both the public and private sectors typically save around half of a windfall gain resulting from a price rise. We argue that private windfalls should be left with the private sector rather than taxed. The focus of policy towards windfalls should be monetary rather than fiscal. The central bank should accommodate aggregate changes in the demand for financial assets. The private sector will initially wish to increase its claims on the central bank as it saves the windfall, but will then reduce them as portfolios are switched into real assets.